Analisis Jaringan Wireless untuk Rumah Kos Menggunakan Router - Fitrian, Harry Pribadi; Putri, Najwa Annisa; Ikhsan Amrillah Arsy; Da’ifa Maulana; Muhamad Luthfi Almanfaluthi; Zidan Zain Shibghatullah (Universitas Methodist Indonesia, 2025)
As the number of users and digital activities increases, the need for quality internet networks in boarding houses is also increasing. However, Wi-Fi networks in boarding houses face challenges in the form of multi-story buildings with concrete walls, long corridors, and many small rooms, coupled with the high number of connected devices and differences in the characteristics of the 2.4 GHz and 5 GHz frequencies, which cause dead spots, decreased throughput, and increased delay during peak hours. This study uses a Systematic Literature Review method on 15 studies related to indoor Wi-Fi network design, bandwidth management, and Quality of Service analysis in boarding house environments. The results of the study show that the most suitable topology is the application of several access points at the center of the building or main corridor, reinforced by APs or repeaters in areas with high physical barriers, designed using a Top Down Network Design (TDND) approach to align with the needs of residents and the characteristics of the space. From a management perspective, the combination of User Manager, CAPsMAN, and PCQ is effective for authentication, fair bandwidth distribution, and access point load balancing, thereby reducing misuse and preventing overload. Quality of Service parameters such as throughput, delay, jitter, and packet loss are used to compare network conditions before and after optimization, and various studies show that this combination of topology design and bandwidth management consistently improves speed, stability, and equitable Wi-Fi access for boarding house residents.